A Case-Control Study of Comparison of Plasma Levels of Matrix Metalloproteinase-9 in Inhaled Opium Addicts and Clinically Healthy Persons - Maryam Amizadeh; Shahryar Dabiri; Armin Javedan; Ali Eftekharian; Aliasghar Arabi (Addiction and Health, 2017)
cancer invasion and lymphatic metastasis. Smoking has been reported to increase the metalloproteinase level, but the role of opium consumption in metalloproteinase level has not yet been examined. The current research intended to examine the impacts of opium consumption on the serum levels of metalloproteinase.Methods: This case-control research was conducted in Kerman (in the southeast of Iran), after getting medical approve by the ethics committee. Case group of 33 non-smokers with no active inflammatory diseases who had the experience of inhaled opium and its derivatives were compared with a control group of 40 non-smokers with no active inflammatory disease and no experience of inhaled opium and its derivatives. Student’s t-test, mean, and chi-square test were employed to determine the correlation between the variables.Findings: No statistically meaningful variation was detected in plasma metalloproteinase concentration between the case and control groups (P = 0.160). Also, there was no significant relation between the plasma metalloproteinase concentration and urinary morphine in case groups (P = 0.410), but a statistically significant correlation was found between gender and metalloproteinase in both the case and control groups (P = 0.003).